2021
DOI: 10.3389/fimmu.2021.739430
|View full text |Cite
|
Sign up to set email alerts
|

Human Complement C4B Allotypes and Deficiencies in Selected Cases With Autoimmune Diseases

Abstract: Human complement C4 is one of the most diverse but heritable effectors for humoral immunity. To help understand the roles of C4 in the defense and pathogenesis of autoimmune and inflammatory diseases, we determined the bases of polymorphisms including the frequent genetic deficiency of C4A and/or C4B isotypes. We demonstrated the diversities of C4A and C4B proteins and their gene copy number variations (CNVs) in healthy subjects and patients with autoimmune disease, such as type 1 diabetes, systemic lupus eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 60 publications
(124 reference statements)
0
17
0
Order By: Relevance
“…This includes, for instance, the C4A and C4B isotypes of complement factor 4, which cannot be distinguished by affinitybased platforms (Supplementary Table 5). Their sequences differ in less than one percent, but this greatly affects their binding affinity towards their molecular targets 40 . Of the remaining pQTLs, 61% were replicated in at least five studies (Extended Data Fig.…”
Section: Novel Pqtls Link Proteins To Gwas Resultsmentioning
confidence: 99%
“…This includes, for instance, the C4A and C4B isotypes of complement factor 4, which cannot be distinguished by affinitybased platforms (Supplementary Table 5). Their sequences differ in less than one percent, but this greatly affects their binding affinity towards their molecular targets 40 . Of the remaining pQTLs, 61% were replicated in at least five studies (Extended Data Fig.…”
Section: Novel Pqtls Link Proteins To Gwas Resultsmentioning
confidence: 99%
“…We postulate that activated C4A and C4B proteins interfere and balance each other’s effects physiologically to achieve optimum defence against infections and autoimmunity and mitigate collateral damages due to complement-mediated injuries of self-tissue. C4A deficiency, which is also indicated by low copy numbers of C4T or C4L, and higher proportion of C4B among total C4 ( C4B/C4T ), would disturb such dynamic equilibrium and skew the immune response towards inflammation and autoimmunity with generation of autoantibodies 25 32…”
Section: Discussionmentioning
confidence: 99%
“…C4A deficiency, which is also indicated by low copy numbers of C4T or C4L, and higher proportion of C4B among total C4 ( C4B/C4T ), would disturb such dynamic equilibrium and skew the immune response towards inflammation and autoimmunity with generation of autoantibodies. 25 32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C4B was an opsonin that covalently binds complement-activating targets ( Mayilyan et al, 2008 ). Recent studies have reported that diversities of C4A and C4B proteins and their gene copy number variations (CNVs) in healthy subjects and patients with autoimmune diseases ( Zhou et al, 2021 ). Our results demonstrated that the expression of C4B was also significantly elevated in the urine of active SLE, and was positively correlated with disease activity.…”
Section: Discussionmentioning
confidence: 99%